A framework for integrating geospatial information systems and hybrid cloud computing. (April 2018) - Helmi, Abdelrahman M.; Farhan, Marwa S.; Nasr, Mona M.
Abstract: Many decisions are made daily based on the simple mental processing. This way of decision making is suitable for the simple personal daily issues. But when decisions are concerned with general and sensitive sectors, this way of decision making is unacceptable. Nowadays, Geospatial Information Systems help in making more accurate decisions in a lot of sections that would be built on accurate information by way of drawing maps and visualizing data to clearly judge which option is the best for that particular situation. This paper raises a framework that integrates the Geospatial Information Systems with the Hybrid Cloud Computing to let them work together and get greater powerful benefits via applying the concept of cloud computing to overcome the flaws related to the desktop GIS including the huge startup cost and the storage capacity and to provide the feature of location independence accessibility where the GIS can be accessed from anywhere and anytime. The hybrid cloud computing was picked to be integrated with the GIS to gain the elasticity and security of dealing with different types of data; private and public data. This integration is presented in three dimensions. The first one is architecture with seven segments that illustrate the main structure for the Hybrid Cloud GIS within a mix of private environment and public environment. The second one is the types of the participants and their workflow within the two environments. The last dimension is a case study for applying this integration in the health sector in Egypt.